Analisis Stereotipe Gender Dalam Budaya Pemerkosaan Sebagai Rekomendasi Kebijakan Pemerintah - Nova Riyanti; Desy Selawaty; Triwik Puji Rahayu (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2019)
Gender is an issue that is always interesting to cover. In its development, gender has always been related to female emancipation words, not only at the level of society at the macro level or at the inter-state level. A poor understanding of gender and sex makes this a refractive gender. The purpose of this study was to convey, explore and analyze gender stereotype in a rape culture that flourished in Indonesian society and made recommendations to the Government. In this case, through literature review, researchers used a qualitative approach to being able to express existing issues and get a deep picture of gender stereotypes issues in the growing rape culture in Community. Researchers voted to use a qualitative descriptive approach in this study. Then, the emphasis of the qualitative approach used is in terms of the phenomenological approach. Researchers have determined the informant needed in this study. In addition, researchers are trying to choose the informant who understands the problem even experiences sexual harassment and feels the impact of the stereotype of gender and rape culture that happened to him. The current phenomenon is difficult to change, but awareness of the importance of the battle of injustice must be fought. The government needs to examine legislation to suppress harassment and sexual violence that continue to increase annually. Then, the community and foundations of this existing victim mentoring need to be supported even need to expand the mentoring to the various areas in Indonesia, especially in the district/city.